Effects of simulated drought on the carbon balance of Everglades short‐hydroperiod marsh. (23rd April 2013) - Malone, Sparkle L.; Starr, Gregory; Staudhammer, Christina L.; Ryan, Michael G.
Abstract: Hydrology drives the carbon balance of wetlands by controlling the uptake and release of CO2 and CH4 . Longer dry periods in between heavier precipitation events predicted for the Everglades region, may alter the stability of large carbon pools in this wetland's ecosystems. To determine the effects of drought on CO2 fluxes and CH4 emissions, we simulated changes in hydroperiod with three scenarios that differed in the onset rate of drought (gradual, intermediate, and rapid transition into drought) on 18 freshwater wetland monoliths collected from an Everglades short‐hydroperiod marsh. Simulated drought, regardless of the onset rate, resulted in higher net CO2 losses net ecosystem exchange (NEE) over the 22‐week manipulation. Drought caused extensive vegetation dieback, increased ecosystem respiration ( R eco ), and reduced carbon uptake gross ecosystem exchange (GEE). Photosynthetic potential measured by reflective indices (photochemical reflectance index, water index, normalized phaeophytinization index, and the normalized difference vegetation index) indicated that water stress limited GEE and inhibited R eco . As a result of drought‐induced dieback, NEE did not offset methane production during periods of inundation. The average ratio of net CH4 to NEE over the study period was 0.06, surpassing the 100‐year greenhouse warming compensation point for CH4 (0.04). Drought‐induced diebacks of sawgrass (C3 ) led to the establishment of the invasive species torpedograss (C4 ) when water was resupplied. These changes in the structure and function indicate that freshwater marsh ecosystems can become a net source of CO2 and CH4 to the atmosphere, even following an extended drought. Future changes in precipitation patterns and drought occurrence/duration can change the carbon storage capacity of freshwater marshes from sinks to sources of carbon to the atmosphere. Therefore, climate change will impact the carbon storage capacity of freshwater marshes by influencing water availability and the potential for positive feedbacks on radiative forcing.